Advancements in the diagnosis and treatment of renal epithelioid angiomyolipoma: A narrative review. Issue 10 (3rd September 2022) - Yang, Jian‐Wei; Liang, Cheng; Yang, Li
Abstract: Renal epithelioid angiomyolipoma (EAML) is a unique subtype of angiomyolipoma that contains a variety of cytoplasmic‐rich, eosinophilic cytoplasm epithelioid cells in addition to mature adipocytes, hyaline thick‐walled vessels, and smooth muscle‐like spindle cells. In recent years, increasing evidence has shown that EAML is a potentially malignant tumor. Due to the lack of typical clinical manifestations and imaging features, it is difficult to diagnose before surgery, and the diagnosis mainly depends on postoperative histopathological examination. With the advancement of pathological diagnostic techniques, more EAML cases has been discovered, but clinicians still lack a comprehensive understanding of EAML. This review comprehensively describes some pathological and clinical features of EAML, with special attention to the pathogenesis and treatment of malignant EAML in order to assist with clinical diagnosis and treatment.